KAJIAN LITERATUR INOVASI PEMBELAJARAN SAINS DI MASA PANDEMI COVID - Muhdi Harto; Misbah Misbah (FKIP ULM, 2020)
The world of education is again disturbed by the massive spread of the COVID-19 virus or coronavirus disease. The use of technology is considered to facilitate and be a solution and innovation in the learning process that can be a way out so that the teaching and learning process during the COVID-19 period becomes more effective. One of the innovations that teachers can do as educators in delivering learning materials is using models in collaboration with technological advances in the learning process, especially in science learning. This research is descriptive in the form of a literature study. Data sources come from 15 scientific articles from national journals and accredited national journals. Based on the literature review that has been carried out, it can be concluded that the use of online learning models in collaboration with technology such as the Zoom platform, google classroom, WhatsApp, and others can be used in the science learning process at all levels of education during the COVID-19 pandemic. This is because this learning model is centred on students so that they are not dependent on the teacher, which is in line with the basis of online learning, which requires students to think critically, be active in exploring or understanding the subject matter presented. Students are required to establish communication between fellow students and the teacher who acts as a moderator.Keywords: Covid-19; Inovations; Online Learning; Science Dunia pendidikan kembali terusik dengan adanya penyebaran virus COVID-19 atau coronavirus disease secara masif. Penggunaan teknologi dianggap bisa mempermudah dan menjadi solusi serta inovasi dalam proses pembelajaran yang bisa menjadi jalan keluar sehingga proses belajar mengajar di masa COVID-19 menjadi lebih efektif. Salah satu inovasi yang bisa dilakukan guru sebagai tenaga pendidik dalam menyampaikan materi pembelajaran yaitu penggunaan model yang dikolaborasikan dengan kemajuan teknologi dalam proses pembelajaran khususnya pada pembelajaran sains. Penelitian ini merupakan penelitian deskriptif berupa studi kepustakaan. Sumber data berasal dari 15 artikel ilmiah dari jurnal nasional maupun jurnal nasional terakreditasi. Berdasarkan kajian literatur yang telah dilakukan, dapat disimpulkan bahwa penggunaan model pembelajaran online leaning yang dikolaborasikan dengan teknologi seperti platform Zoom, google classroom, whatsapp, dan lainnya dapat digunakan dalam proses pembelajaran sains pada semua jenjang pendidikan di masa pandemi COVID-19. Hal ini karena model pembelajaran ini berpusat kepada peserta didik sehingga mereka tidak ketergatungan kepada guru, yang sejalan dengan dasar dari pembelajaran secara daring yaitu menuntut peserta didik untuk berpikir kritis, aktif dalam menjelajahi atau memahami materi pelajaran yang disampaikan serta peserta didik dituntut agar dapat menjalin komunikasi yang baik antara sesama peserta didik dan juga guru yang berperan sebagai moderator.Kata kunci: Covid-19; Inovasi; Online Learning; Sains